2021
DOI: 10.1002/pen.25840
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized PVA film with good adsorption capacity for anionic dye

Abstract: The dye-water treatment by polyvinyl alcohol (PVA) is still a challenge as PVA is characterized by its strong affinity to water. Therefore, this study aims to fabricate a functional PVA film with good regeneration ability to remove anionic dyes from aqueous solution using polyamidoamine dendrimers (PAMAM) as a modifier and epichlorohydrin as a cross-linker. Solution casting technique was applied to prepare the functionalized film. The adsorption efficiency of the film was evaluated by studying the effect of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Protonation of the adsorption sites occurs at low pH. As pH of the solution increases in acidic medium (2)(3)(4)(5)(6), number of ═N + H À groups decrease and number of the neutral ═N groups present on the surface of the particles increase, which ultimately increases CTC adsorption in the acidic medium. CTC adsorption by modified RF aerogel revealed that samples modified with PmPDA contained a large number of ═N groups that showed the sensitivity to CTC adsorption in pH range of 2-6.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Protonation of the adsorption sites occurs at low pH. As pH of the solution increases in acidic medium (2)(3)(4)(5)(6), number of ═N + H À groups decrease and number of the neutral ═N groups present on the surface of the particles increase, which ultimately increases CTC adsorption in the acidic medium. CTC adsorption by modified RF aerogel revealed that samples modified with PmPDA contained a large number of ═N groups that showed the sensitivity to CTC adsorption in pH range of 2-6.…”
Section: Effect Of Phmentioning
confidence: 99%
“…[1] Water resources are prone to be polluted in various ways by different compounds like pharmaceuticals. [2][3][4] These chemicals are a threat and concern for clean drinking water sources and human/animal health. [5] In recent past years, drugs have been continuously discharged into aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, remediation of contaminated water from synthetic dyes is considered one of the most important challenges facing all countries due to the harmful effects of these dyes on the environment [1,2]. Synthetic dyes, industrial raw materials, are found in wastewater as a result of improper discharge of dyes from the textile, leather, paper, rubber, plastics, and pharmaceuticals industries [3,4]. The presence of these dyes in wastewater stream can lead to many environmental problems as they have carcinogenic and mutagenic properties on living organisms even at low concentrations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the removal of these dyes before they are discharged into various water bodies has become an essential step [7]. Several methods have been tested for removing toxic dyes from wastewater such as biological, ion exchange, advanced oxidation, coagulation, flocculation, ultra-filtration through membranes, and adsorption methods [3,6,8]. Adsorption method has received great attention among other methods due to its cost-effective, highly efficient, easy operation, simple design and availability of a wide range of adsorbent materials [1,3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation